Practical microfinance : a training manual - Harper, Malcolm (London : ITDG, 2003)
Practical Microfinance provides material and detailed step-by-step guides for twenty-two sessions, including case studies, quantitative exercises and field trips. Its covers topics such as sustainability, interest rates, the choice of delivery methodologies and institutions, impact assessment and delinquency management.
Includes bibliographical references (p. 178-180) and index.
nmn 03/05/13;osa15/05/13, ijb 26/02/2019
Loans
Keywords: Microfinance; Microfinance